Carbon Dioxide Adsorption by Calcium Zirconate at Higher Temperature - K. B. Kale; R. Y. Raskar; V. H. Rane; A. G. Gaikwad (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
The CO2 adsorption by calcium zirconate was explored at pre- and post- combustion temperature condition. The several samples of the calcium zirconate were prepared by different methods such as sol-gel, solid-solid fusion, template and micro-emulsion. The samples of the calcium zirconate were characterized by measurement of surface area, alkalinity/acidity, and recording the XRD patterns and SEM images. The CO2 adsorptions by samples of the calcium zirconate were studied in the temperature range 100 to 850 oC and the CO2 adsorptions were observed in the ranges of 6.88 to 40.6 wt % at 600 0C and 8 to 16.82 wt% at in between the temperatures 200 to 300 oC. The effect of Ca/Zr mol ratio in the samples of the calcium zirconate on the CO2 adsorption and alkalinity were discussed. The adsorbed moisture by the samples of the calcium zirconate was found to be useful for the CO2 adsorption. The promoted the samples of the calcium zirconate by K+, Na+, Rb+, Cs+, Ag+ and La3+ showed the increased CO2 adsorption. The exposure time of CO2 on the samples of the calcium zirconate showed the increased CO2 adsorption. The samples of the calcium zirconate were found to be regenerable and reusable several times for the adsorption of CO2 for at the post- and pre-combustion temperature condition. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)